Interaksi Sistem Pengendalian Intern Dengan Faktor-Faktor Yang Berpengaruh Terhadap Kualitas Laporan Keuangan Pemerintah Daerah Kabupaten Klaten - Hadi, Ryan Chrisna; , Dr. Zulfikar, SE, M.Si (2016)
Based on the report of the Board of Audit of the financial statements Klaten regency government in fiscal year 2014 to get opinions "Fair With Exceptions". The purpose of this study were (1) To analyze the Effect of Implementation of the Government Accounting Standards, Financial Management, Accounting Staff Competence on the Quality of Local Government Finance Report. (2) To analyze interactions affect the Internal Control System Implementation of the Government Accounting Standards, Financial Management, Accounting Staff Competence on the Quality of Local Government Finance Report. Object of this research is a Civil Servant Klaten regency government. The research sample of 54 respondents from 18 SKPD. Sempel retrieval techniques using purposive sampling. The test data is done by testing the validity and reliability test and classical assumption in use is the normality test, heteroscedasticity, multikolenearitas test. Hypothesis testing using multiple regression analysis, t-test, R2 and F test Research results Application of the Government Accounting Standards do not affect the quality of Government Financial Statements, Financial Management and Accounting Staff Competence affect the quality of Local Government Finance Report. Interactions affecting the internal control system of Financial Management and Accounting Staff Competence on the Quality of Local Government Finance Report.